The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00415-020-09719-1
|View full text |Cite
|
Sign up to set email alerts
|

Sub-angiographic peripheral emboli in high resolution DWI after endovascular recanalization

Abstract: Background and aim To analyze the incidence of peripheral emboli after successful mechanical thrombectomy (MT) of intracranial large vessel occlusions (LVO). Methods We performed a prospective analysis of patients with intracranial LVO who underwent successful MT and received a 1.5 T MRI including diffusion-weighted imaging (DWI) in standard-and high-resolution as well as susceptibility-weighted imaging (SWI) on the day following the intervention. Reperfusion grade was assessed on post-thrombectomy digital sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Recently, we found that peripheral ischemic lesions resulting from these emboli can frequently be detected on high-resolution diffusion-weighted imaging (DWI) despite supposed complete reperfusion in DSA (10). The assessment of potentially superior treatment techniques or predictors of outcome following MT by standard outcome or imaging measures requires a large patient cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that peripheral ischemic lesions resulting from these emboli can frequently be detected on high-resolution diffusion-weighted imaging (DWI) despite supposed complete reperfusion in DSA (10). The assessment of potentially superior treatment techniques or predictors of outcome following MT by standard outcome or imaging measures requires a large patient cohort.…”
Section: Introductionmentioning
confidence: 99%
“…15 The lack of associated DWI changes suggests most if not all the SWI abnormalities were nonobstructing, whereas in the study of emboli from thrombectomy of intracranial large vessel occlusion, the SWI abnormalities were associated with larger DWI changes as well. 16 MRI J o u r n a l P r e -p r o o f susceptibility-weighted imaging may be a more sensitive test of embolism and may have value in future safety studies.…”
Section: Discussionmentioning
confidence: 99%
“…First, the first-pass effect could be real and the number of retrievals increases the risk of vessel injury and subsequent symptomatic intracranial hemorrhage (sICH) [19][20][21]; however, we did not observe a statistically significant increased number of sICH in our study, although this comparison K might lack statistical power due to the small number of patients in our cohort. Furthermore, each retrieval attempt is associated with risk of dispersing small distal emboli, which could lead to impaired clinical outcome [22,23]. Other possible reasons include the prolonged procedure time, the need for induction of general anesthesia and increased amounts of contrast agents [24,25].…”
Section: Discussionmentioning
confidence: 99%